Sub-optimal pH Preadaptation Improves the Survival of Lactobacillus plantarum Strains and the Malic Acid Consumption in Wine-Like Medium - Succi, Mariantonietta; Pannella, Gianfranco; Tremonte, Patrizio; Tipaldi, Luca; Coppola, Raffaele; Iorizzo, Massimo; Lombardi, Silvia Jane; Sorrentino, Elena (Frontiers in Microbiology, 2017)
Forty-two oenological strains of Lb. plantarum were assessed for their response to ethanol and pH values generally encountered in wines. Strains showed a higher variability in the survival when exposed to low pH (3.5 or 3.0) than when exposed to ethanol (10 or 14%). The study allowed to individuate the highest ethanol concentration (8%) and the lowest pH value (4.0) for the growth of strains, even if the maximum specific growth rate (μmax) resulted significantly reduced by these conditions. Two strains (GT1 and LT11) preadapted to 2% ethanol and cultured up to 14% of ethanol showed a higher growth than those non-preadapted when they were cultivated at 8% of ethanol. The evaluation of the same strains preadapted to low pH values (5.0 and 4.0) and then grown at pH 3.5 or 3.0 showed only for GT1 a sensitive μmax increment when it was cultivated in MRS at pH 3 after a preadaptation to pH 5.0. The survival of GT1 and LT11 was evaluated in Ringer's solution at 14% ethanol after a long-term adaptation in MRS with 2% ethanol or in MRS with 2% ethanol acidified at pH 5.0 (both conditions, BC). Analogously, the survival was evaluated at pH 3.5 after a long-term adaptation in MRS at pH 5.0 or in MRS BC. The impact of the physiologic state (exponential phase vs stationary phase) on the survival was also evaluated. Preadapted cells showed the same behavior of non-preadapted cells only when cultures were recovered in the stationary phase. Mathematical functions were individuated for the description of the survival of GT1 and LT11 in MRS at 14% ethanol or at pH 3.5. Finally, a synthetic wine (SW) was used to assess the behavior of Lb. plantarum GT1 and LT11 preadapted in MRS at 2% ethanol or at pH 5.0 or in BC. Only GT1 preadapted to pH 5.0 and collected in the stationary phase showed constant values of microbial counts after incubation for 15 days at 20°C. In addition, after 15 days the L-malic acid resulted completely degraded and the pH value increased of about 0.3 units.